2015
DOI: 10.2478/pjs-2014-0082
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Outcome of Treatment of Postoperative Primarily Closed Sternotomy Wounds Treated Using Negative Pressure Wound Therapy

Abstract: Hospital infections, and in particular infections of the surgical site are a common problem of the procedural departments. Due to continuous progress of surgical techniques and patient population getting older with multiple co-morbidities, multidirectional actions need to be taken to avoid these infections or, if they do occur, achieve optimal treatment outcomes. Vacuum wound therapy is one of the directions that has been developed over the recent years.evaluate wound healing in patients after an off-pump coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 17 publications
4
50
0
Order By: Relevance
“…This study's findings are comparable to previous study2014 that compared negative wound pressure dressing to conventional dressing [42]. A fewer number of patients required dressing.…”
Section: Antibioticssupporting
confidence: 81%
See 2 more Smart Citations
“…This study's findings are comparable to previous study2014 that compared negative wound pressure dressing to conventional dressing [42]. A fewer number of patients required dressing.…”
Section: Antibioticssupporting
confidence: 81%
“…In this study, 100% of the infected cases and 100% of non-infected cases used antibiotics. These results support of the last study in 2014 that found 10% of patients having conventional wound dressing received antibiotics, but none of the patients who received negative pressure wound therapy [42]. And 92.3% of the patients receiving negative pressure wound therapy heal without complications, eliminating the need for antibiotics compared to 77.5% receiving conventional dressing [42].…”
Section: Antibioticssupporting
confidence: 78%
See 1 more Smart Citation
“…These treatment protocols declared that the portable devices could be administered to patients presenting an ASA score higher than 2 or an IRI higher than 3. It should be noted that the portable device efficacy was derived from the most recent and updated literature evidence available 12,18,27,28…”
Section: Methodsmentioning
confidence: 99%
“…Although the effectiveness of the portable device has been amply reported in literature,12,18,27,28 and is shown to be more effective compared with traditional NPWT, little is known with regard to the economic impact of its introduction and consequent adoption into clinical practice.…”
Section: Introductionmentioning
confidence: 99%